Seasonal PM Management: ( I ) What Emissions Should be Reduced? 미세먼지 계절관리제: ( I ) 어떤 배출물질을 줄여야 하는가? - Kang, Yoon Hee; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2022)
In this study, the impacts of 50% and 100% reductions in domestic SO2, NOX, NH3, VOCs, and primary PM2.5 (PPM2.5) emissions on PM2.5 concentrations in South Korea during the 2nd seasonal PM management period (i.e., from December 2020 to March 2021) were estimated with air quality modeling based on the Clean Air Policy Support System 2018 emissions inventory. For the first half (0 → 50%) emission reduction, PPM2.5 is the most effective pollutant to lower the nationwide PM2.5concentration (2.3 μg/m3), followed by NH3 (1.5 μg/m3), NOX (1.0 μg/m3), VOC (0.7 μg/m3), and SO2 (0.2 μg/m3. However, the impacts of NH3 and NOX emissions for the second half (50 → 100%) emission reductions on the nation-wide PM2.5 concentrations significantly increased to 6.3 μg/m3 and 4.5 μg/m3, respectively, which surpassed the impact of PPM2.5 reduction (2.3 μg/m3) for the same magnitude of emission reduction. The zero-out contribution of SO2 emissions remained as low as 0.5 μg/m3. This result exhibits significant nonlinear responses of PM2.5 concentrations to its precursor emission changes from domestic emission sources. The estimated nonlinearities (=ΔPM2.5 to the second half emissions reduction/ΔPM2.5 to the first half emission reduction) for the domestic NOX, NH3, SO2, PPM2.5, and VOCs emissions were 4.6, 4.1, 1.7, 1.0, and 0.8, respectively. Our study results indicate that the sensitivity and nonlinear response of PM2.5 concentrations to the precursor emissions should be considered when developing an air quality improvement plan because the effectiveness of PM2.5 precursors in lowering PM2.5 concentrations vary depending on the magnitudes of the emission reductions to achieve a targeted PM2.5 level.
Keywords: Nonlinearity index; Pm2.5; Precursors; Seasonal pm management; Sensitivity